Primary Care: Clinics in Office Practice, Exercise Testing - Evans, Corey H. (Harcourt Brace and Company, 1994)
The purpose of this book is to give primary care physicians a current summary of exercise testing in a format that provides practical information on the performance, interpretation and multiple uses of the procedure.
Keywords: Exercise Testing; Non-Fiction; Therapeutics